Reversed Conversion, Theodicy, and Cross-cultural Mission in Shūsaku Endō's Silence and Zhenyun Liu's Someone to Talk To - Li, Jin (Christianity & literature, 2022)
To present the complex relationship between Christianity and modern non-Western societies, this article compares two novels from East Asia, Silence (1966) by Japanese writer Shūsaku Endō and Someone to Talk To (2009) by Chinese novelist Liu Zhenyun, that touch on themes of Christianity and cross-cultural tensions in indigenous contexts, including theodicy, suffering, and hope. Endō portrays a Japanese society through the eyes of a western Catholic priest. In comparison, Liu's literary innovation presents a possibility of missionary integration through humanly mundane details of life.